Analysis of Built-Up Land Utilization and Management of Flood-Resilient Settlement in Bireuen Regency - Sugiarti, Annisa Sri; Sunarty, Risma (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2023)
The expansion of built-up areas in Bireuen Regency has shown a significant trend in recent years, in line with the growth of settlements and regional infrastructure. This trend indicates increasing pressure on open spaces, particularly in areas highly vulnerable to disasters. This study aims to analyz the changes in built-up land between 2019 and 2023 and to identify its relationship with flood-prone zones. The method employed is spatial analysis using a Geographic Information System (GIS) based overlay approach, combining built-up land maps derived from land cover data with flood hazard index maps issued by BNPB. The data used include administrative boundaries, built-up land data for 2019 and 2023, and flood hazard maps. The analysis reveals that northern areas of Bireuen Regency, such as Kota Juang, Peusangan, and Samalanga Subdistricts, experienced notable expansion in built-up areas, most of which are located within moderate to high flood hazard zones. This development reflects a pattern of land use that has not adequately considered disaster risk aspects. On the other hand, central and southern regions such as Peudada, Peusangan Selatan, and Peulimbang show lower levels of vulnerability and offer safer spatial development opportunities. These findings indicate a mismatch between actual land use and spatial allocation outlined in spatial planning documents (RTRW), as well as weak enforcement in controlling development in high-risk zones. Therefore, there is a need to integrate spatial planning policies with disaster risk maps in every planning process. Furthermore, it is essential to strengthen settlement governance through adaptive, risk-based approaches, continuous use of spatial data, and strict enforcement of zoning regulations. This study not only provides empirical insights into regional vulnerability but also serves as a crucial reference in formulating disaster mitigation strategies, controlling land conversion, and promoting the development of resilient and sustainable human settlements.